IDEALISME DAN REALISME DALAM PARADIGMA FATWA EKONOMI SYARIAH DI INDONESIA - Dwi Novaria Misdawati; Athoillah Islamy (Jurnal Asy-Syukriyyah, 2022)
This normative-philosophical research uses the theory of idealism and realism of Islamic law in identifying the epistemological features of the DSN-MUI paradigm. The results of the study show that the epistemological pattern of the paradigm of the formulation of the DSN-MUI integrates the idealism and realism of Islamic law. This integration can be seen from the four DSN-MUI paradigms. First, al-Taysîr al-Manhaji. This paradigm emphasizes the formulation of fatwas to use legal opinions that do not burden legal subjects, but still adhere to the correct methodology of Islamic law. Second, at-Tafriq baina al-Halal wal Haram. This paradigm emphasizes the separation of halal and haram issues, both in terms of capital, product development, and profit. This is because Islamic economic activities cannot be completely separated from the conventional economic system that has been running for a long time. Third, I'adah al-Nazhar. This paradigm emphasizes reviewing the opinions of classical Islamic law when it is seen that it is no longer a solution to the empirical problems of sharia economics in modern society. Fourth, Tahqiq al-Manath. This paradigm emphasizes the evaluation of legal causes (illat law) by considering the reality of the development of the economic system.